Just Say No to the TPP: A Democratic Setback for American and Asian Public Health; Comment on "The Trans-Pacific Partnership: Is It Everything We Feared for Health?" - Carles Muntaner; Deb Finn Mahabir (Kerman University of Medical Sciences, 2017)
The article by Labonté, Schram, and Ruckert is a significant and timely analysis of the Trans-Pacific Partnership (TPP) policy and the severe threats to public health that it implies for 12 Pacific Rim populations from the Americas and Asia (Australia, Brunei, Canada, Chile, Japan, Malaysia, Mexico, New Zealand, Peru, Singapore, United States, and Vietnam). With careful and analytic precision the authors convincingly unearth many aspects of this piece of legislation that undermine the public health achievements of most countries involved in the TTP. Our comments complement their policy analysis with the aim of providing a positive heuristic tool to assist in the understanding of the TPP, and other upcoming treaties like the even more encompassing Transatlantic Trade and Investment Partnership (TTIP), and in so doing motivate the public health community to oppose the implementation of the relevant provisions of the agreements. The aims of this commentary on the study of Labonté et al are to show that an understanding of the health effects of the TPP is incomplete without a political analysis of policy formation, and that realist methods can be useful to uncover the mechanisms underlying TPP's political and policy processes.